Types and Forms of Folk Songs Tradition in Malayalam Literature - S, Kamaraj (International Research Journal of Tamil, 2021)
The folk songs have been well flourished in Malayalam Literature. The Malayalam folk songs entirely different from the Tamil folk songs. But it is fact that the structure of Malayalam Pattu has been adopted from the Tamil Literature and we could understand that the Tamil structure has been following even today. Folk songs have a special place in Malayalam Literature. Folk songs in Malayalam are categorized into community songs, Worship songs, Professional songs and celebration songs etc. This study has been analysis the Types and forms of folk songs which related to worshiped.